2020
DOI: 10.3390/app10093072
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Way to Automatically Plan Cellular Networks Supported by Linear Programming and Cloud Computing

Abstract: With the increasing number of mobile subscribers worldwide, there is a need for fast and reliable algorithms for planning/optimization of mobile networks, especially because, in order to maintain a network’s quality of service, an operator might need to deploy more equipment. This paper presents a quick and reliable way to automatically plan a set of frequencies in a cellular network, using both cloud technologies and linear programming. We evaluate our pattern in a realistic scenario of a Global System for Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The author showed that the approximation and optimal solutions are close in dimension. A linear equation system was set up to config the cell locations and frequencies under the signal-to-interference plus noise ratio (SINR) constraint in [29]. The author used Z-order curve which converts three-dimensional points in geographic areas into unidimensional ones.…”
Section: A Related Workmentioning
confidence: 99%
“…The author showed that the approximation and optimal solutions are close in dimension. A linear equation system was set up to config the cell locations and frequencies under the signal-to-interference plus noise ratio (SINR) constraint in [29]. The author used Z-order curve which converts three-dimensional points in geographic areas into unidimensional ones.…”
Section: A Related Workmentioning
confidence: 99%
“…When transitioning from a link-level perspective to a system-level analysis, we must deal with several other issues, such as distance limitation, signal-to-noise ratio (SNR) degradation, weak coverage areas and blind zones, which are particularly relevant when working in the high-frequency spectrum [11,20,21]. This is the main reason why network and resource allocation planning are crucial when deploying these systems for cellular communications, independently of the scenario under study [11,22]. There are few system-level evaluations of mmWave schemes in the literature, such as the ones mentioned in [23,24], but beyond all the proposals in the field of system-level analysis very few examples have been extended to the 5G New Radio (5G NR) standard of the 3rd Generation Partnership Project (3GPP) and for the THz level (e.g., 100 GHz) as we cover in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…In the planning of cellular resources, an example of this trend in supporting SON by cloud services is presented in [12] [13], a recent investigation proposing an automatic and efficient planning strategy for large cellular Global System for Mobile Communications (GSM) deployments. Although a well-known technology with more than 30 years, commercial available planning tools like Metric Software-as-a-Service (SaaS) [14] are adopting such methodologies.…”
Section: Introductionmentioning
confidence: 99%